Fractional derivatives for vortex simulations - Szekeres, Béla J.; Izsák, Ferenc (Proceedings of the Conference Algoritmy, 2016)
Two modifications of the incompressible Navier--Stokes equations are  investigated.  The first modification is based on assuming hyperviscosity such that the Laplacian operator is replaced with a fractional Laplacian.  The second modification consists of using fractional time derivatives.  Both models are tested on the classical Backward Facing Step benchmark problem with different expansion ratios. The simulation results are in a good accordance with real measurements.